Incidence of childhood cancers in the North East geopolitical zone of Nigeria - Suleiman, Dauda Eneyamire; Adamu, Adamu Saidu; Ezenkwa, Uchenna Simon; Yusuf, Maimuna Orahachi; Lawan, Aliyu Ibrahim; Dachi, Rufai Abdu; Bwala, Kefas John; Liman, Haruna Usman; Kabir, Abba; Adamu, Adamu Isa; Kolomi, Modu Abubakar; Jimoh, Abdulrazaq Ajanaku; et al. (Frontiers in Oncology, 2024)
Background Cancers are a major cause of childhood mortality worldwide especially in LMICs where underdiagnoses and lack of quality cancer data hampers effective cancer control efforts. This study aimed to document and describe the patterns and characteristics of childhood cancers in the North East geopolitical zone of Nigeria.Methods This was a retrospective cross-sectional study that collected cancer data from 4 out of the 6 states in the North East of Nigeria. The data included all malignancies diagnosed in children aged 0-19 years between 2019 and 2022. The age-specific incidence rates were also calculated for the individual 5-year age groups (0-4 years, 5-9 years, 10-14 years, and 15-19 years). The crude incidence rates (CIR) were calculated as the weighted averages of the respective ASRs in each age range within 0-14 years and 0-19 years respectively. The cancers were grouped according to the International Incidence of Childhood Cancers, volume 3 (IICC3).Cancers in people <20 years accounted for 7.3% of all cancers diagnosed over the same period. The crude incidence rates (CIR) for cancers in children and adolescents were 20.9 per million children aged 0-19 years and 18.8 per million children aged 0-14 years respectively, while the age-standardised rates (ASR) were 1.80 and 1.63 per million personyears respectively. There was a variation in the most commonly diagnosed cancers across all age groups. However, lymphomas were the most commonly diagnosed cancers overall, while CNS tumours were overwhelmingly rare.Despite data limitations, this study provides useful insights into patterns of cancers in the region and will hopefully provide a basis for the strengthening of paediatric oncology care, childhood cancer control programmes and population-based cancer registries.